EASYSCANNER: INNOVATING TEST CORRECTION AND OPTIMIZING THE TIME OF TEACHERS AND EDUCATIONAL INSTITUTIONS (CIPEEX, 2025)
Correcting tests is a labor-intensive and time-consuming task in the routine of teachers and educational institutions. To minimize this challenge, EasyScanner emerges as an innovative technological solution: an intuitive mobile application that, through a mobile device's camera, automates the correction of tests and answer keys, providing agility, efficiency, and accuracy to the process. With EasyScanner, teachers and educators can spend less time on manual correction and focus their efforts on essential activities such as lesson planning, developing innovative pedagogical projects, and individualized monitoring of each student's progress, stimulating more personalized and effective teaching. To meet the diverse needs of users, EasyScanner offers two modalities: a free version, with basic functionalities, advertisements, and a correction limit, ideal for familiarization with the tool; and a premium version, with exclusive features, including unlimited test correction and removal of advertisements. Aimed at teachers, educators, schools, colleges, and educational institutions of all sizes and modalities, EasyScanner seeks to modernize the assessment experience, making it more practical, dynamic, and integrated with the technological reality of contemporary education.
Keywords: scan; education; mobile; test correction